2016
DOI: 10.18632/oncotarget.7218
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal bisphenol A exposure induces meiotic arrest and apoptosis of spermatogenic cells

Abstract: Bisphenol A (BPA) is a widely used industrial plasticizer, which is ubiquitously present in the environment and organisms. As an endocrine disruptor, BPA has caused significant concerns regarding its interference with reproductive function. However, little is known about the impact of BPA exposure on early testicular development. The aim of the present study was to investigate the influence of neonatal BPA exposure on the first wave of spermatogenesis. Newborn male mice were subcutaneously injected with BPA (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Subcutaneous injection is an appropriate route for BPA delivery into the neonatal mice to assess its effects on testicular development. The reason why we chose subcutaneous injection as the route of BPA administration was explained in another paper (Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous injection is an appropriate route for BPA delivery into the neonatal mice to assess its effects on testicular development. The reason why we chose subcutaneous injection as the route of BPA administration was explained in another paper (Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [ 48 ] found that BPA could interfere with ERα signaling in the developing hippocampus in an ER-dependent manner. Neonatal BPA exposure disrupted meiosis progression during the first wave of spermatogenesis and increased the expression of ERα and PCNA in the developing testes [ 49 ]. However, few studies have explored the possible mechanisms of how BPA increases ERα expression.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is a cell cycle protein in the nucleus and functions in DNA synthesis ( 32 ). PCNA is commonly used as a marker to assess the state of cell proliferation ( 33 ). The results of the current study demonstrated that ADRP silencing decreased the expression level of PCNA in PDGF-treated VSMCs.…”
Section: Discussionmentioning
confidence: 99%